Library programming with LEGO MINDSTORMS, Scratch, and PicoCricket: analysis of best practices for public libraries. - Suarez Romero J (Computers in Libraries, 2010)
Public libraries are redefining their roles in order to stay relevant to the needs of the communities they serve. The latest advances in technology for children and teens, specifically, robotics sets and media-rich software, are bringing new challenges and opportunities for lifelong learning.